Dimensions of maltreatment and academic outcomes for youth in foster care. (October 2018) - McGuire, Austen; Jackson, Yo
Abstract: Childhood maltreatment is often associated with youth's ability to successfully function in school. Youth with a history of maltreatment often receive lower grades and scores on tests of academic achievement, as well as demonstrate more negative behaviors in school, as compared to non-maltreated youth. However, there are many inconsistencies in previous studies examining the association between maltreatment and academic outcomes in youth. One potential reason for mixed findings within the literature could be a result of how maltreatment is measured and operationalized. The current study examined if the methods used to define and describe maltreatment contribute to the association between maltreatment and academic functioning in youth. Youth in foster care ( N = 490, M age = 13.13[3.09]) were recruited and information on their maltreatment history and academic functioning was obtained from official agencies, school records, and self-reported measures. Using a SEM framework when examining each dimension separately in the same model, results suggested that frequency maltreatment was more predictive of academic behavior, as compared to type and severity. No dimensions were associated with grades and significant findings were only observed for models using self-report data. However, when examined using a measurement model approach, maltreatment as a whole was associated with school behavior, which was found for both self-report and case file measurement models. The findings suggest a need for research on academic functioning to take a comprehensive approach when measuring and defining maltreatment as this may be a more robust and accurate predictor of academic functioning.